Lack of peptide YY signaling in mice disturbs gut microbiome composition in response to high‐fat diet. Issue 4 (22nd March 2021) - Farzi, Aitak; Ip, Chi Kin; Reed, Felicia; Enriquez, Ronaldo; Zenz, Geraldine; Durdevic, Marija; Zhang, Lei; Holzer, Peter; Herzog, Herbert
Abstract: Peptide YY (PYY), produced by endocrine L cells in the gut, is known for its critical role in regulating gastrointestinal functions as well as satiety. However, how these processes are integrated with maintaining a healthy gut microbiome composition is unknown. Here, we show that lack of PYY in mice leads to distinct changes in gut microbiome composition that are diet‐dependent. While under chow diet only slight differences in gut microbiome composition could be observed, high‐fat diet (HFD) aggravated these differences. Specifically an increased abundance of the Bacteroidetes phylum with a corresponding decrease of the Firmicutes/Bacteroidetes ratio could be detected in Pyy‐ knockout (KO) mice in response to HFD. Detailed analysis of the Bacteroidetes phylum further revealed that the Alistipes genus belonging to the Rikenellaceae family, the Parabacteroides belonging to the Tannerellaceae family, as well as Muribaculum were increased in Pyy‐ KO mice. In order to investigate whether these changes are associated with changed markers of gut barrier and immunity, we analyzed the colonic expression of various pro‐inflammatory cytokines, as well as tight junction proteins and mucin 2, and identified increased mRNA expression of the tight junction proteins Cldn2 and Ocel1 in Pyy‐ KO mice, while pro‐inflammatory cytokine expression was not significantly altered. Together these results highlight a critical gene‐environment interaction between diet and the gut microbiome and its impact on homeostasis of the intestinal epithelium under conditions of reduced PYY signaling which is commonly seen under obese conditions.